1972
DOI: 10.1108/eb022143
|View full text |Cite
|
Sign up to set email alerts
|

E. & J. DAVIS TRANSPORT LTD. v. D. CHATTAWAY AND OTHERS

Abstract: July 27, 1972 Master and Servant — Redundancy — Dismissal — Wage agreement dispute — One day strike by employees — Company's refusal of work on old terms — Refusal of new terms — Dismissals — Whether lock‐out — Repudiation of employees' contracts — Whether redundancy self‐induced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Preliminary results from X‐HESS indicate that: The normalΓprefix−logλEdd$$ \Gamma -\log {\lambda}_{\mathrm{Edd}} $$ distribution of high‐λEdd$$ {\lambda}_{\mathrm{Edd}} $$ AGN is characterized by a large scatter in terms of normalΓ$$ \Gamma $$, showing values of the photon index less steep than those expected from previously reported correlations (e.g. Brightman et al 2013; Liu et al 2021; Risaliti et al 2009; Shemmer et al 2008), in agreement with what we found in our recent X‐ray spectroscopic analysis of a sample of fourteen high‐λEdd$$ {\lambda}_{\mathrm{Edd}} $$ AGN Laurenti et al (2022). Remarkable spectral and flux variations are observed in the first X‐HESS sources we have already analyzed.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Preliminary results from X‐HESS indicate that: The normalΓprefix−logλEdd$$ \Gamma -\log {\lambda}_{\mathrm{Edd}} $$ distribution of high‐λEdd$$ {\lambda}_{\mathrm{Edd}} $$ AGN is characterized by a large scatter in terms of normalΓ$$ \Gamma $$, showing values of the photon index less steep than those expected from previously reported correlations (e.g. Brightman et al 2013; Liu et al 2021; Risaliti et al 2009; Shemmer et al 2008), in agreement with what we found in our recent X‐ray spectroscopic analysis of a sample of fourteen high‐λEdd$$ {\lambda}_{\mathrm{Edd}} $$ AGN Laurenti et al (2022). Remarkable spectral and flux variations are observed in the first X‐HESS sources we have already analyzed.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, a long‐standing issue consists in the existence of a positive correlation between the photon index of the X‐ray power‐law continuum normalΓ$$ \Gamma $$ and λEdd$$ {\lambda}_{\mathrm{Edd}} $$, implying a very steep continuum (i.e., normalΓ>2$$ \Gamma >2 $$) is a prerogative of AGN with λEdd$$ {\lambda}_{\mathrm{Edd}} $$ 0.3em0.3$$ \kern0.3em \gtrsim 0.3 $$ (e.g. Brightman et al 2013; Fanali et al 2013; Huang et al 2020; Liu et al 2021; Risaliti et al 2009; Shemmer et al 2008). This is often explained in terms of an enhanced UV emission from the disc, that improves the efficiency of the radiative cooling in the X‐ray corona and, consequently, leads to the reduction of the electron temperature, resulting in an overall steepening of the power‐law continuum.…”
Section: Correlation With X‐ray Propertiesmentioning
confidence: 99%
See 1 more Smart Citation